PERANCANGAN X-BANNER , SPANDUK DAN KARTU NAMA SEBAGAI MEDIA PROMOSI PADA PT. NITI SEGARA TRANS - Puteri Anindya Maulan; Neilin Nikhlis; Dendy Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2021)
Developments in the business of shipping goods are very tight, many similar companies offer varioustypes of delivery services. Creating promotional strategies to attract consumers, various ways of promotingmust be done to win the competition.PT. Niti Segara Trans is a company engaged in the delivery of goods or often called an expedition.Because companies need the right promotional tools. So there are obstacles in the delivery of information.In this case, we need a media that can remind, be effective (faster in spreading), and efficient (require lesstime and effort).cost ).Because the company wants to grow faster and more consumers know PT. Niti Segara Trans, theauthor wants to promote PT. Niti Segara Trans by using X-Banner, Banner, and business card media. Thepurpose of making X-Banners, business cards, and banners as promotional media for outside the company.With brochures, consumers can read what is offered by PT. Niti Segara Trans. With a consumer businesscard, it will be easier to store and remember the address of PT. Niti Segara Trans. While the use of thebanner itself as a promotional medium used to provide brief information to the public to get to know PT.Niti Segara Trans.With this kind of promotion, it is hoped that PT. Niti Segara Trans will be more advanced and knownby the wider community